The Impact of B/D Ratio on the Technical Performance of Outrigger Fishing Vessels at PPN Palabuhanratu - Hamka, Moh. Saiful Rahman; Novita, Yopi; Kurniawati, Vita Rumanti (International Journal of Marine Engineering Innovation and Research, 2024)
Small and slender boats are usually installed with outrigger as additional construction to enhance its stabilities. The same practices are found in Palabuhanratu fishing port. The massive use of outrigger in most fishing ports, including Palabuhanratu, have led to berthing problems due to limited area of the port basin, hence boat or outrigger modification is required to overcome the problem. Adjusting the hull slenderness by defining the proper breadth and depth (B/D) ratio can be potential approach to eliminate the outrigger. Therefore, this research is designed to define ideal B/D ratio for boat without outrigger based on its stability, resistance and seakeeping in accordance with operational purpose. The study was conducted by simulating three different B values with constant D, each of which experiencing two different operational conditions, half and full loads. The quality of boat stability was evaluated in five parameters defined by IMO, whilst the resistance performance was evaluated using comparison analysis, and the seakeeping performance was evaluated using wave height and wave arrival angle. The result showed that according to its operational purposes, the boat with B/D ratio of 1,71 has the best performance to be operated without outrigger